2017
DOI: 10.1001/jamaoncol.2016.3067
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Prevalence of Human Papillomavirus (HPV) in Head and Neck Squamous Cell Cancers by Sex, Race, Anatomic Tumor Site, and HPV Detection Method

Abstract: During 1995 through 2012, the proportion of OPSCCs caused by HPV has increased significantly. This increase was not restricted to white men but was a consistent trend for women and men, as well as for white and nonwhite racial groups. Few non-OP HNSCCs were HPV related. P16 positivity was a good surrogate for ISH+ tumor status among OPSCC, but not a good surrogate for non-OP HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 24 publications
8
127
0
Order By: Relevance
“…While OPSCC incidence remains lower among Hispanic than White men, it is steadily increasing among Hispanic men in parallel fashion to White men with dramatic increase in recent years (2006-2014: APC 5.4, p=0.003). Prior work has shown that prevalence of HPV-positive tumors has increased over time across races 6 , indicating that HPV is also driving incidence trends among these other racial groups. Among Blacks, the proportion of OPSCC caused by HPV is increasing 6 , suggesting the dramatic reduction in incidence of OPSCC among Blacks driven by reduction in tobacco and alcohol related cancers would be even larger if not for the increasing contribution of HPV-positive cancers in Blacks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While OPSCC incidence remains lower among Hispanic than White men, it is steadily increasing among Hispanic men in parallel fashion to White men with dramatic increase in recent years (2006-2014: APC 5.4, p=0.003). Prior work has shown that prevalence of HPV-positive tumors has increased over time across races 6 , indicating that HPV is also driving incidence trends among these other racial groups. Among Blacks, the proportion of OPSCC caused by HPV is increasing 6 , suggesting the dramatic reduction in incidence of OPSCC among Blacks driven by reduction in tobacco and alcohol related cancers would be even larger if not for the increasing contribution of HPV-positive cancers in Blacks.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that prevalence of HPV-positive tumors has increased over time across races 6 , indicating that HPV is also driving incidence trends among these other racial groups. Among Blacks, the proportion of OPSCC caused by HPV is increasing 6 , suggesting the dramatic reduction in incidence of OPSCC among Blacks driven by reduction in tobacco and alcohol related cancers would be even larger if not for the increasing contribution of HPV-positive cancers in Blacks. Among women, the previous racial disparity in OPSCC incidence between Whites and Blacks no longer exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that the prevalence of HPV was different among all racial groups [26]. Previous studies showed that HPV infection is strongly correlated with p16 overexpression in LSCC [4].…”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancermentioning
confidence: 92%
“…[1][2][3] This rising incidence is attributed to oncogenic human papillomavirus (HPV). 7,9,10 Whether these trends apply more broadly in the United States is unknown. 7,9,10 Whether these trends apply more broadly in the United States is unknown.…”
Section: Introductionmentioning
confidence: 99%